2016
DOI: 10.1080/09712119.2016.1256293
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein electrophoretic pattern in dairy cows during the periparturient period

Abstract: This study was aimed at the evaluation of changes in the concentrations of serum protein fractions in 10 clinically healthy dairy cows in the period from 1 week before to 6 weeks after calving. Serum was analysed for total protein concentrations, and the relative and absolute values of protein fractionsalbumin, alpha 1-(α 1), alpha 2-(α 2), beta 1-(β 1), beta 2-(β 2), and gamma-(γ) globulins. The concentrations of total proteins increased significantly from week 1 before parturition till the end of the sixth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
3
8
0
1
Order By: Relevance
“…In the present study, significantly higher A/G ratio was observed on 4 th week of lactation compared to 12 th week in Amrit Mahal, Holstein Friesian crossbred and Jersey crossbred cows (Table 1). These findings were in corroboration with the reports of Russell and Roussel (2007) in ruminants and Tothova et al, (2018) in dairy cows. However, Kaneko et al, (1997) reported fairly constant levels of A/G ratio in healthy cattle.…”
Section: Resultssupporting
confidence: 92%
“…In the present study, significantly higher A/G ratio was observed on 4 th week of lactation compared to 12 th week in Amrit Mahal, Holstein Friesian crossbred and Jersey crossbred cows (Table 1). These findings were in corroboration with the reports of Russell and Roussel (2007) in ruminants and Tothova et al, (2018) in dairy cows. However, Kaneko et al, (1997) reported fairly constant levels of A/G ratio in healthy cattle.…”
Section: Resultssupporting
confidence: 92%
“…Pregnancy is considered to be a period of severe metabolic and protein alterations in the body (59). The decrease in plasma protein level with the advancement of gestation in the control group was due to the high demand for amino acids, which were transferred from the mother to the developing fetus for the synthesis of numerous proteins required for the proper growth of the fetus and for the maintenance of a healthy pregnancy (60). The high protein profile of MOLP makes it an ideal substitute for rapeseed and soybean meals for ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Foremilk and milk contain proteins derived from plasma and tissue in addition to milk-specific proteins (Wall et al 2015). Serum albumin is the most abundant plasma protein, and concentrations of serum albumin in mammary secretions are used for estimating the permeability of the blood-milk barrier (Wall et al 2015;Tóthová et al 2016). Immunoglobulins are important milk components for udder and calf health (Maunsell et al 1999).…”
Section: Introductionmentioning
confidence: 99%